Investigation of spectra and of aggregation of vanadium phtalocyanine molecules in two-component solutions - Piryatinskii, Yu.; Antypov, I.; Tarasenko, S.; Yatsun , O. (Energy and Automation, 2025)
It was studied the electronic spectra of vanadium phtalocyanine dye molecules in diluted and concentrated solutions as well as in low- and high-polarity solvents. In diluted low-polarity solvent VOPc molecules exist in monomer state, whereas dye molecules concentration increase leads to appear of dimer formation. It was shown that using of mixed acid-water solvent is an effective approach to controlled aggregation of dye molecules. Main parameters of the influence on VOPc aggregation are concentration of water ingredient and associates “growth” time. In a concentrated high-polarity solvent, the dye molecule is in the form of a monocation solvated by solvent molecules and unable to interact with other dye ones. In this case, it is just the monomolecular absorbance spectrum that is characteristic for the solution. As water is added, the dye molecular interaction becomes possible due to the solvatic shell destruction, and association of organic molecules occurs. In our case, this results in the appearance of a broad 980 nm band in the absorbance spectrum. Using acid-water mixtures and varying the water concentration therein, the dye aggregation process can be controlled as well as the number of molecules in an aggregate. So the appearance of absorbance bands at 775 and 690 nm is observed which can be attributed to the formation of sandwich-type dimers (H-dimers). As the water concentration increases, large dye aggregates are formed. At high water concentrations, micro-scale single crystals may grow. The “growth” process can be observed in absorbance spectra as the appearance of the 980 nm band and its further intensity increase, long-wavelength shift and broadening. Above features demonstrate an approach to size-controlled preparation of dye molecules aggregates in polar – non-polar solutions mixture for farther use in photovoltaic and sensors applications. Key words: nano-size organic dye crystals, association of dye molecules, enhancement of electronic properties of aggregated dye molecules, seft-assembling of molecules